2015
DOI: 10.1039/c4cc05329j
|View full text |Cite
|
Sign up to set email alerts
|

Separation of xylenes by enclathration

Abstract: The isomers of xylene have been separated by enclathration using three host compounds: 9,9'-bianthryl (H1), 9,9'-spirobifluorene (H2) and trans-2,3-dibenzoylspiro[cyclopropane-1,9-fluorene] (H3). The structures of each host with a single xylene isomer have been elucidated and, for H1, the relative lattice energies of the clathrates with ortho- and para-xylene have been evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 18 publications
0
29
0
Order By: Relevance
“…sql-1-Co-NCS therefore exhibits ad ifferent sorption mechanism than that observed in other OX-selective MOMs such as the MIL-53 family,which exhibit breathing from open (narrow-pore) to more open (largepore) structures. [24] Indeed, it is this clay-like behavior that enables the high adsorption capacity of sql-1-Co-NCS is related to the enclathration approach taken by Nassimbeni et al [7,25] It also means that there is little structural distortion in either the closed or open phases of sql-1-Co-NCS,w hich helps to explain its recyclability.…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…sql-1-Co-NCS therefore exhibits ad ifferent sorption mechanism than that observed in other OX-selective MOMs such as the MIL-53 family,which exhibit breathing from open (narrow-pore) to more open (largepore) structures. [24] Indeed, it is this clay-like behavior that enables the high adsorption capacity of sql-1-Co-NCS is related to the enclathration approach taken by Nassimbeni et al [7,25] It also means that there is little structural distortion in either the closed or open phases of sql-1-Co-NCS,w hich helps to explain its recyclability.…”
Section: Methodsmentioning
confidence: 98%
“…Recently, a supermolecular cage with intrinsic porosity reported by Cooper's group exhibits exceptionally high selectivity but it also suffers from low adsporption capacity . Nassimbeni and co‐workers have also reported inclusion compounds with high selectivity but low working capacity . Indeed, there is no physisorbent material which combines the desirable criteria (selectivity >5 and capacity >50 wt %) that would enable a paradigm shift towards physisorptive separation of C 8 aromatics.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the inclusion of acetonitrile leads to a molecular arrangement allowing photodimerisation, whilst the methanol solvate hinders this. 23 In other studies, inclusion has been utilised to separate xylenes 24 showing a clear preference of one guest over another, 25 or to store volatile guests. 26,27 Inclusion complexes have recently become focus of attention to study the incorporated molecules, either in an unusual conformation, 28 or to obtain structural information of a hard to crystallise compound.…”
Section: Introductionmentioning
confidence: 99%
“…Ethylbenzene (EB) is mainly produced by alkylation of benzene with ethylene,b ecause it is extremely energy-intensive to isolate it by superfractionation with more than 300 theoretical plates. [7] Indeed, there is no physisorbent material which combines the desirable criteria (selectivity > 5and capacity > 50 wt %) that would enable aparadigm shift towards physisorptive separation of C 8 aromatics. 10-20 wt %) and selectivity (ca.…”
mentioning
confidence: 99%